Cluster Formation Effect of Water on Pristine and Defective MoS2 Monolayers - Kangli Wang; Beate Paulus (Nanomaterials, 2023)
The structure and electronic properties of the molybdenum disulfide (MoS2) monolayer upon water cluster adsorption are studied using density functional theory and the optical properties are further analyzed with the Bethe–Salpeter equation (BSE). Our results reveal that the water clusters are electron acceptors, and the acceptor tendency tends to increase with the size of the water cluster. The electronic band gap of both pristine and defective MoS2 is rather insensitive to water cluster adsorbates, as all the clusters are weakly bound to the MoS2 surface. However, our calculations on the BSE level show that the adsorption of the water cluster can dramatically redshift the optical absorption for both pristine and defective MoS2 monolayers. The binding energy of the excitons of MoS2 is greatly enhanced with the increasing size of the water cluster and finally converges to a value of approximately 1.16 eV and 1.09 eV for the pristine and defective MoS2 monolayers, respectively. This illustrates that the presence of the water cluster could localize the excitons of MoS2, thereby greatly enhance the excitonic binding energy.